A poesia de Cecília Meireles em busca do rosicler - Costa, Soraya Borges (2011)
This study investigates the imaginary in Metal rosicler by Cecilia Meireles, one of her last books which was published in 1960. The aim is to analyze the relation of this book and the structures of alchemy imaginary. As well as the spiritual alchemists searched for the transmutation of insignificant metal in order to make it possible for men to reach the enlightenment, in Metal rosicler there is the attempt to go through an ontological search by linking the poetic to the alchemy symbolism, then as it happens in the alchemy process, it reveals itself in the rosicler (the color of a rose). Started by poetry, the search indicates the transmutation of the black stone- the raw rosicler metal- revealing from the depth a hidden and sublime essence in alchemy rosicler. Such essence is the meaningful reason for the search because it represents the desirable entirety in coincidentia oppositorum, and also the integration of the opposites of androgeny. Thus, the transformation may only be completed by performing the phases and the steps in the alchemy ritual: mortification in the nigredo, the abstract ideality in the albedo leading to the whole life of red color in the rubedo. All the symbolism untwines itself before the mitocriticism of poems which is based on contributions of critique about imaginary and alchemy, such as: the imaginary anthropology, according to Gilbert Durant`s work; phenomenology of poetic, as stated by Carl Gustav Jung studies. The theoretical instrument purposed by Durand e Bachelard concerns the imagination s dynamic creation and the strength of myths in peoples representative productions throughout the years. Imaginary philosophy of alchemy is based on Jung s deep psychology perspective which considers the relation between the alchemy symbolism and the process of individualization of human being in the search of entirety of himself. Mitocriticism work reveals the constellation of images which is a response for the alchemy poetic of the book, how the symbols imbricate the imperishable into ephemeral; the nocturnal images which join life and death; images of the air, the water, and the land which brings in the transcendence; dissolution in the nigredo and molding the androgynous, besides the mithemes of Hermes-Mercury in the alchemy become, the symbols of mortification of black stone and the sublimination of rosicler in the rubedo. Therefore, such journey reveals, in poems, the poetic melting pot of transmutation where the lyrical itself searches the spiritual entirety in the extraction of rosicler.